2022
DOI: 10.1002/anie.202201432
|View full text |Cite
|
Sign up to set email alerts
|

The SARS‐CoV‐2 Spike Glycoprotein Directly Binds Exogeneous Sialic Acids: A NMR View

Abstract: The interaction of the SARS CoV2 spike glycoprotein with two sialic acid‐containing trisaccharides (α2,3 and α2,6 sialyl N‐acetyllactosamine) has been demonstrated by NMR. The NMR‐based distinction between the signals of those sialic acids in the glycans covalently attached to the spike protein and those belonging to the exogenous α2,3 and α2,6 sialyl N‐acetyllactosamine ligands has been achieved by synthesizing uniformly 13C‐labelled trisaccharides at the sialic acid and galactose moieties. STD‐1H,13C‐HSQC NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 61 publications
3
51
0
Order By: Relevance
“…A very recent study revealed that the S protein on SARS-CoV-2 recognizes oligosaccharide containing SAs, with a strong preference for monosialylated gangliosides 12 . Another study supplied a first experimental demonstration of the presence of a α2,3- and α2,6- sialyl N -acetyllactosamine binding site in the NTD of the S1 19 . Here we will focus on 9- O -acetylated-SA (9-AcSA) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study revealed that the S protein on SARS-CoV-2 recognizes oligosaccharide containing SAs, with a strong preference for monosialylated gangliosides 12 . Another study supplied a first experimental demonstration of the presence of a α2,3- and α2,6- sialyl N -acetyllactosamine binding site in the NTD of the S1 19 . Here we will focus on 9- O -acetylated-SA (9-AcSA) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…These results imply that the topology around the H69, Q183, and S247 sites in sarbecovirus spike may play important roles in binding with saccharides. During the preparation of the manuscript, an NMR study demonstrated that the NTD of SARS-CoV-2 spike binds exogenous (α2,3)/(α2,6)-Neu5Ac linked to N -acetyllactosamine, and the galactose moieties display additional contributions for the binding ( 18 ). However, in our study, we found neuraminidase cleavage would not abolish the binding of SARS-CoV-2 and other sarbecovirus S-NTDs to BSM.…”
Section: Discussionmentioning
confidence: 99%
“…The sialic acid-binding function in transmissible gastroenteritis virus (TGEV) has been suggested to influence viral pathogenicity ( 14 16 ), and computational modeling suggests sialic acid binding in SARS-CoV-2 spike may be an immune evasion mechanism ( 17 ). Recent studies also propose that sialic acid or 9- O -Ac sialic acid of glycoproteins and glycolipids might be served as the host factor for SARS-CoV-2 infection ( 18 22 ). However, the functional analysis of this phenotype was not fully assessed in cell culture or animal models, leaving the biological impact unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports that the spike protein can recognize structures with sialic acid, as shown in a study where saturation transfer difference nuclear magnetic resonance (STD NMR) was used revealing that the N-terminal domain is capable of interacting with α2,3 sialyl N-acetyllactosamine and α2,6 sialyl N-acetyllactosamine trisaccharides, with preference when the sialic acid is bound by the α2,3 bond [ 92 ]. In another study, it was observed that protein S binds sialylated gangliosides with a similar affinity with which it recognizes HS.…”
Section: Sars-cov-2mentioning
confidence: 99%